Biblical hermeneutics in ancient Ukrainian literature - Білоус, Петро Васильович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
Review of the monograph by Natalia Levchenko “Biblical hermeneutics in ancient Ukrainian literature”.Kharkiv: Maidan, 2018. – 392 p.